2009
DOI: 10.1007/s00213-009-1754-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic clozapine treatment improves prenatal infection-induced working memory deficits without influencing adult hippocampal neurogenesis

Abstract: Our findings do not support the hypothesis that the atypical antipsychotic drug clozapine may influence cognitive functions by acting on adult neurogenesis in the hippocampus, regardless of whether the drug is administered to subjects with or without a neurodevelopmental predisposition to adult neuropathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 78 publications
2
27
1
Order By: Relevance
“…Studies on similar animal models have revealed that OLZ performs promitotic activity [29], increases the number of newly formed cells in the hippocampus and SVZ [28,39] and prevents neuronal loss in this region [37]. Similar neurogenic effects are reported for other atypic neuroleptics like clozapine and risperidon [28,38,40,50], as well as antidepressants, for example fluoxetine [39,41].…”
Section: Discussionmentioning
confidence: 60%
“…Studies on similar animal models have revealed that OLZ performs promitotic activity [29], increases the number of newly formed cells in the hippocampus and SVZ [28,39] and prevents neuronal loss in this region [37]. Similar neurogenic effects are reported for other atypic neuroleptics like clozapine and risperidon [28,38,40,50], as well as antidepressants, for example fluoxetine [39,41].…”
Section: Discussionmentioning
confidence: 60%
“…Since a role of PLs in axonal growth and sprouting is suggested by studies showing synthesis of PC, PE, and SM within axons (46,47), PL changes after injury in the hippocampi may be associated with self-reparative processes. As the hippocampus is a key site for neurogenesis (48,49), it is also possible that an increase in PLs within the hippocampi of injured mice is due to increased neurogenesis (50). Clearly, these Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…However haloperidol had no effect on neurogenesis in the adult dentate gyrus in several studies, using several doses and treatment regimens and examining long-term survival of new neurons as well as their generation (Halim et al, 2004;Malberg et al, 2000;Wakade et al, 2002;Wang et al, 2004). Similarly, atypical antipsychotics like olanzapine, risperidone, and clozapine were also ineffective at altering adult neurogenesis in several studies (Green et al, 2006;Meyer et al, 2010;Wakade et al, 2002;Wang et al, 2004). One study demonstrated an increase in proliferation with clozapine treatment, but the new cells were lost within 3 weeks, likely before becoming functional, despite ongoing clozapine treatment (Halim et al, 2004).…”
Section: Schizophreniamentioning
confidence: 99%